Some Aspects of Pashtun Culture - Ehsanullah Pamir; Asadullah Waheedi; Khalid Ahmad Habib (RIRAI Publisher, 2023)
Pashtun culture is a rich and diverse culture that has been shaped by centuries of history and tradition. Often referred to as Pashtunwali, this culture encompasses every aspect of daily life, from social norms and customs to religious practices and cuisine. As an ethnic group, the Pashtun people are primarily located in Afghanistan and Pakistan. They are known for their proud and distinctive culture that emphasizes loyalty, hospitality, and respect for the Pashtun code of conduct. A central aspect of Pashtun is the Pashtunwali, which is the traditional code of conduct of the Pashtun people. Derived from the Pashto language, this code emphasizes concepts like courage, honor, and hospitality, and serves as a guide for how Pashtuns should conduct their lives. Hospitality is one of the most valued traits in Pashtun culture, and guests are treated with the utmost respect and care. This tradition dates back to the times of the ancient Silk Road, when traveling merchants of all backgrounds would stop at the Pashtuns' homes and receive food, shelter, and care. Music and dance are also cherished in Pashtun culture, with traditional instruments like the rubab (a lute-like instrument) and tabla (a percussion instrument) used to create melodic and rhythmic pieces. The attan, a traditional dance, is common at weddings, religious festivals, and other celebrations. The Pashtuns are a primarily Muslim community, and religion is deeply ingrained in their culture. Islamic practices like praying five times a day, fasting during Ramadan, and giving to charity are all important parts of life for Pashtuns. However, Pashtunwali also places a strong emphasis on tolerance and respect for other religions, and there is a long history of coexistence between different faiths in the region.